DEMOKRASI DAN PEMBANGUNAN POLITIK - Effendy, Muhadjir (Jurnal Bestari, 1991)
"Power tends to corrupt those who wield it, and absolute power tends to corrupt absolutely," is the famous adagium of the leading political scientist, Lord Action. The history of the countries in the world can be considered as the "manifestation" of that adagium. How is the role and the contribution of Islam in this case? You will find the answer in the following article. One of the "final" conclusion is that islam tends to stress the Muslim leaders high commitment to its teachings.